The Development and Validation of the Compassion Scale - Pommier, Elizabeth; Neff, Kristin D.; Tóth-Király, István (Assessment (Odessa, Fla.), 2020)
This article presents a measure of compassion for others called the Compassion Scale (CS), which is based on Neff’s theoretical model of self-compassion. Compassion was operationalized as experiencing kindness, a sense of common humanity, mindfulness, and lessened indifference toward the suffering of others. Study 1 (n = 465) describes the development of potential scale items and the final 16 CS items chosen based on results from analyses using bifactor exploratory structural equation modeling. Study 2 (n = 510) cross-validates the CS in a second student sample. Study 3 (n = 80) establishes test–retest reliability. Study 4 (n = 1,394) replicates results with a community sample, while Study 5 (n = 172) replicates results with a sample of meditators. Study 6 (n = 913) examines the finalized version of the CS in a community sample. Evidence regarding reliability, discriminant, convergent, construct, and known-groups validity for the CS is provided.